Pseudomonas infection, allergy, and cystic fibrosis. Issue 8 (August 1982) - Pitcher-Wilmott, R W; Levinsky, R J; Gordon, I; Turner, M W; Matthew, D J
Abstract : The clinical significance of the high prevalence of positive immediate skin tests in cystic fibrosis is unclear. Using analysis of variance, we have tested the hypothesis that patients with allergic cystic fibrosis have worse lung disease than non-allergic patients. Clinical data, skin prick tests, total or specific IgE antibody levels, chest radiographs, and pulmonary function tests were obtained in 104 cystic fibrosis patients. Patients with positive immediate skin reactions to at least one allergen were more likely to be persistently colonised by Pseudomonas aeruginosa than skin test negative patients. The skin test positive patients were also significantly older (mean difference 2.15 years). Analysis of variance showed that pseudomonas infection was the most significant factor contributing to lung damage and the effect of allergy was not significant. Similar longitudinal analysis of pulmonary function over 5 years and study of the hospital admission rate showed that the only statistically significant factor associated with deterioration was colonisation with P. aeruginosa.